2009
DOI: 10.4081/jlimnol.2009.251
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the 70 kDa Heat shock protein family in Alpine freshwater chironomids (Diptera, Chironomidae) under natural conditions

Abstract: Chironomidae represent up to 100% of the fauna of Alpine streams. Because they survive stress conditions such as extremely low
temperature (annual mean <4 °C), these animals represent a good organism model to analyze the relationship between adaptation to
cold and expression of stress proteins such as the 70 kDa Heat shock protein family. Fourth instar larvae of ten species of coldstenothermal
chironomids (Pseudodiamesa branickii, Diamesa latitarsis, D. laticauda, D. cinerella, D. insignipes, D.…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This clearly indicates that such midges employ the HSP70 protein family in their physiological adaptation to cold waters of their natural habitat. This was also detected in other alpine cold stenothermal midges (Lencioni et al, 2009) and in the Antarctic midge B. antarctica (Rinehart et al, 2006). The strategy of expressing hsp genes continuously is adopted by other several organisms belonging to animals and protists living in very cold environments of polar and temperate zones to avoid protein denaturation due to low temperatures (Joplin et al, 1990;Yocum et al, 1991;Denlinger et al, 1992;Lee et al, 1995;Feder and Hofmann, 1999;Carpenter and Hofmann, 2000;La Terza et al, 2001;Place and Hofmann, 2005).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This clearly indicates that such midges employ the HSP70 protein family in their physiological adaptation to cold waters of their natural habitat. This was also detected in other alpine cold stenothermal midges (Lencioni et al, 2009) and in the Antarctic midge B. antarctica (Rinehart et al, 2006). The strategy of expressing hsp genes continuously is adopted by other several organisms belonging to animals and protists living in very cold environments of polar and temperate zones to avoid protein denaturation due to low temperatures (Joplin et al, 1990;Yocum et al, 1991;Denlinger et al, 1992;Lee et al, 1995;Feder and Hofmann, 1999;Carpenter and Hofmann, 2000;La Terza et al, 2001;Place and Hofmann, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…During this period, the quantity of suspended sediments reaches 350 mg/l and the mean summer water temperature is 3.2 • C, whereas in winter, when the substrate is partially frozen, it gets down to subzero (Boscaini et al, 2004). Therefore, the growing season is brief and the zoobenthic community is composed mainly of chironomids of the genus Diamesa that has the physiological (Lencioni et al, , 2008 and biochemical (present study; Lencioni et al, 2009) adaptations to withstand environmental stresses such as low temperature of water. In the stream reach at lower altitude (1260 m a.s.l.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Few environmental factors have a larger influence on insect metabolism than temperature (Ward & Stanford, 1979; Sweeney, 1984; Danks, 2007). A number of studies suggest changes in the structure, function and activity of enzymes and enzymatic processes in chironomids as a response to different temperatures (Detra & Collins, 1986; Simcic, 2005; Lencioni, Boschini & Rebecchi, 2009). Other studies have demonstrated that temperature increases chironomid respiration rate (Edwards, 1958; Johnson & Brinkhurst, 1971; Konstantinov, 1971; McFarlane & McLusky, 1972; Ripley, 1980; Iwakuma, 1986; Bairlein, 1989; Hamburger & Dall, 1990; Hamburger, Dall & Lindegaard, 1994; Simcic, 2005; Brodersen et al , 2004; Lencioni et al , 2008).…”
Section: Temperature Influence On Chironomid Physiology and Behamentioning
confidence: 99%
“…Pseudodiamesa branickii and D. cinerella represent two exceptions because they both show constitutive expression of the inducible isoform of 70‐kDa HSP genes under natural conditions (control samples). These results are consistent with previous data obtained in this laboratory, highlighting the synthesis and accumulation of the HSP70 proteins under natural conditions in both species (Lencioni et al ., ). Presumably, these midges have evolved a molecular mechanism to maintain hsp function without interfering with central metabolism and growth (which requires the synthesis of other proteins), as well as a control mechanism involving environmental or physiological signals that maintains the hsp70 gene in a constant transcriptionally active state, with the aim of preserving protein homeostasis of the cell, as previously observed in Antarctic fish (Place & Hofmann, ).…”
Section: Discussionmentioning
confidence: 97%